2017
DOI: 10.1016/j.mhpa.2017.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative investigation of the role of collaborative football and walking football groups in mental health recovery

Abstract: Efforts to increase physical activity levels in people with serious mental health conditions are viewed as desirable but little is known about how best to support this group to engage in exercise over extended periods. From a personal recovery perspective, the dominant paradigm in current mental health service delivery, one promising route involves participation with, rather than administration to or supervision of, mental health service users in team sports, usually football, in order to foster sharing of com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(54 citation statements)
references
References 30 publications
(11 reference statements)
3
47
0
Order By: Relevance
“…Social support is a frequently used strategy in PA interventions to enhance behaviour change and peer support has been found to aid recovery amongst those with mental health problems who play football (Lamont et al, 2017;Magee, et al, 2015). The current study added that using social support could be essential for engagement in football on the occasions where there were significant barriers to attending.…”
Section: Self-control Strategiesmentioning
confidence: 81%
See 2 more Smart Citations
“…Social support is a frequently used strategy in PA interventions to enhance behaviour change and peer support has been found to aid recovery amongst those with mental health problems who play football (Lamont et al, 2017;Magee, et al, 2015). The current study added that using social support could be essential for engagement in football on the occasions where there were significant barriers to attending.…”
Section: Self-control Strategiesmentioning
confidence: 81%
“…Facilitators to engaging people with mental health problems in football, include the competition element (Lamont et al, 2017) and provision being away from the clinical environment (Magee et al, 2015). One non-clinical environment which has potential to engage people with mental health problems is the provision of football delivered by professional football clubs through their community foundations and trusts (Curran et al 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous small-scale investigations have shown that walking football is a feasible and sustainable exercise intervention that may improve participants' mental wellbeing (Lamont, Harris, McDonald, Kerin, & Dickens, 2017;McEwan et al, 2019;Reddy et al, 2017), as well as their body composition and physical fitness (Arnold, Bruce-Low, & Sammut, 2015). An ethnographic study of walking football suggested that walking football also provides intangible benefits, including increasing participants' 'appetite for life' and enhancing their social engagement as part of a wider supportive community (Loadman, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Also, sport may reduce BMI and promote a higher level of physical health [5,6]. Enjoyment and amusement are very important parts of sport activities [7,8] and that could help patient adherence. More recent evidence [9] have shown a positive effect of sport on schizophrenia symptoms.…”
Section: Introductionmentioning
confidence: 99%